If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4 + 3x) = 3(x + 1) + 11 (4 * 2 + 3x * 2) = 3(x + 1) + 11 (8 + 6x) = 3(x + 1) + 11 Reorder the terms: 8 + 6x = 3(1 + x) + 11 8 + 6x = (1 * 3 + x * 3) + 11 8 + 6x = (3 + 3x) + 11 Reorder the terms: 8 + 6x = 3 + 11 + 3x Combine like terms: 3 + 11 = 14 8 + 6x = 14 + 3x Solving 8 + 6x = 14 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 8 + 6x + -3x = 14 + 3x + -3x Combine like terms: 6x + -3x = 3x 8 + 3x = 14 + 3x + -3x Combine like terms: 3x + -3x = 0 8 + 3x = 14 + 0 8 + 3x = 14 Add '-8' to each side of the equation. 8 + -8 + 3x = 14 + -8 Combine like terms: 8 + -8 = 0 0 + 3x = 14 + -8 3x = 14 + -8 Combine like terms: 14 + -8 = 6 3x = 6 Divide each side by '3'. x = 2 Simplifying x = 2
| -(-1-5)+8=-17+2x | | 2(a+12)=4(a+6)-2a | | 6(2z-3)-4=3(5z-7) | | y+3(15-25)+25=40 | | -56x^3y^4-32x^6y^3= | | m/16=0.5 | | (4x^2-9)/(2x^2-3x) | | 3p-q=3.6 | | x+(x+12)=90 | | 4x^2-16x-y^2-2y+8z^2+8z+17=0 | | 26x^2-23xy+5y^2= | | 336-8x=13x | | 2p=-q+49 | | -1(x-6)=8x-72 | | j/12=11 | | y+2(5-25)+20=30 | | 2x^2-0=64 | | h/13=13 | | 4x^2-16x-y^2-2+8z^2+8z+17=0 | | 6x+3=2x-7-2x | | 40x^2-140=500 | | V=s^3 | | x^2+15xy+54y^2= | | 6n^2+30n-9=0 | | 2y-3-678=500 | | 6x+15x^2+6x^3=0 | | 3x+13=6y | | u^2-12u-15=0 | | 6/t^3=0 | | 6/t^3 | | 6x+-2+8=x+5 | | s^3+4*s^2+10*s+40=0 |